Evaluating the efficiency of environmentally friendly magnetic photocatalyst for the treatment of industrial effluents containing dye pollutants - Sedigheh Abbasi (Applied Water Science)
Abstract In this research, nanocomposites based on two-dimensional nanostructures such as graphene oxide were used as photocatalysts to remove methyl orange. One of the most important advantages of this type of photocatalyst is its high efficiency in the decomposition of colored organic pollutants, as well as its ease of separation at the end of the process. For this purpose, titania semiconductor is synthesized as photocatalytic nanoparticles by hydrolysis method on the surface of graphene oxide. The dependence of photocatalytic activity of nanocomposite and hybrid without graphene oxide on operating conditions including irradiation time and photocatalyst concentration shows the positive effect of these two factors on the removal efficiency of methyl orange. By increasing the irradiation time from 5 to 40 min and also changing the photocatalyst concentration from 0.05 to 0.2%wt, the photocatalytic activity increases significantly, while with the increase in the pH of the suspension from 3 to 11, the removal efficiency initially decreases and then increases. The statistical findings indicate that independent single factors, their binary and triple interactions have a significant effect on the response at the 5% confidence level. Therefore, the statistical models proposed by nanocomposite and hybrid are able to estimate the dependence of removal efficiency on significant factors with an accuracy of 99%. Also, the Box–Cox curve confirms the adequacy of the statistical models without any transformation function.